Selected Attribute of Households and Social Pattern: A Case Study of Ravi River Basin in Himachal Pradesh, India - Sharma, Nikesh (European Journal of Life Safety and Stability (2660-9630), 2022)
This paper is an attempt to analyse the social pattern of 87 villages located in Ravi River basin in Himachal Pradesh. These rural settlements totally depend upon particularly on primary activities and natural environment for their basic needs and income regeneration. The people of the present research area reside in the laps of nature. This study investigates nature and design of dwellings and social condition of these villages. Is geographical factors affects their household pattern? Where climatic conditions are very harsh due to mostly mountainous temperate climatic region? To answer these above following questions, field visit of the same area has been conducted. This research paper is descriptive in nature. Data were collected from the entire 87 villages through questionnaire, interviews, informal discussions and field observation. On the context of households, there were higher compositions of joint families rather than nuclear families. There is lack of adequate of social infrastructure such as education and health institutions. In this basin 83.68% surveyed Villages have educational facilities. The 77.76 % School’s has Playground facility in Ravi River basin in Himachal Pradesh. In this basin only 43.39% Villages has Pucca Road facility due to dissected topography. It is found out from field work that only 27.87% surveyed Villages has Hospital or Dispensary facilities. In this basin about 71% people are involves in Agriculture/Horticulture activities and only 4.82 percent people are in government services. Only 11.11% people have various types of vehicles in this Basin. In this basin 92.40% people are engaged in primary and 7.46% people of this basin are engaged in tertiary activities. In this basin 45 percent houses are pucca, 38 percent mixed and 17 percent houses are kutcha type. In this basin 96.36% household have bathroom and toilet facilities. In Ravi basin 97.50% people belongs to Hindu Religion and 2.5 percent people of this basin have Muslim faith. In this basin 75.46 percent families have livestock in surveyed villages. The paper will be helpful in carrying out the further analysis and showing a way to improve existing socio-economic conditions and household pattern rural settlement in high Himalayan mountainous region in Himachal Pradesh.